Technical Note: Application of positive matrix factor analysis in heterogeneous kinetics studies utilizing the mixed-phase relative rates technique - Y. Liu; Li, S. -M.; Liggio, J. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2014)
The mixed-phase relative rates approach for determining aerosol particle organic heterogeneous reaction kinetics is often performed utilizing mass spectral tracers as a proxy for particle-phase reactant concentration. However, this approach may be influenced by signal contamination from oxidation products during the experiment. In the current study, the mixed-phase relative rates technique has been improved by combining a positive matrix factor (PMF) analysis with electron ionization aerosol mass spectrometry (unit-mass resolution), thereby removing the influence of m/z fragments from reaction products on the reactant signals. To demonstrate the advantages of this approach, the heterogeneous reaction between OH radicals and citric acid (CA) was investigated using a photochemical flow tube coupled to a compact time-of-flight aerosol mass spectrometer (C-ToF-AMS). The measured heterogeneous rate constant (k(2)) of citric acid toward OH was (3.31 +/- 0.29) x10(-12) cm(3) molecule(-1) s(-1) at 298K and (30 +/- 3) % relative humidity (RH) and was several times greater than the results utilizing individual m/z fragments. This phenomenon was further evaluated for particulate-phase organophosphates (triphenyl phosphate (TPhP), tris-1,3-dichloro-2-propyl phosphate (TDCPP) and tris-2-ethylhexyl phosphate (TEHP)), leading to k(2) values significantly larger than previously reported. The results suggest that heterogeneous kinetics can be significantly underestimated when the structure of the products is highly similar to the reactant and when a non-molecular tracer is measured with a unit-mass resolution aerosol mass spectrometer. The results also suggest that the heterogeneous lifetime of organic aerosol in models can be overestimated due to underestimated OH uptake coefficients. Finally, a comparison of reported rate constants implies that the heterogeneous oxidation of aerosols will be dependent upon a number of factors related to the reaction system, and that a single rate constant for one system cannot be universally applied under all conditions.